Effect of Left and Right Nostril Breathing on Heart Rate Variability among Healthy Adult Males: A Cross-sectional Study (International Journal of Physiology, 2020)
The effects of various breathing manoeuvres on autonomic functions, especially those of alternate nostrilbreathing and single nostril breathing have been well documented.1,2,3,4 However, most of the studies haveinvestigated these effects after practiced breathing manoeuvres,5,6,7 and few have looked into the immediateeffects of such types of breathing. The purpose of this study was to determine the immediate effects of asingle session of single nostril breathing, first right nostril and then left nostril, on the various time andfrequency domain parameters of heart rate variability (HRV) and to compare these effects with that of HRVduring normal breathing.Sixty male volunteers (age range, 20 to 40 years) were assessed. Electrocardiography was conducted, usingstandard procedure, under controlled laboratory conditions, for three five-minute periods: during breathingnormally through both nostrils, during the last five minutes of a twenty-minute session of breathing throughthe right nostril only and similarly while breathing through the left nostril only. The R-R intervals obtainedwere analyzed for HRV parameters and further analyzed using different statistical method.When compared to right nostril breathing, a statistically significant increase in mean R-R intervals was notedwith left nostril breathing (p = 0.009). Sympathetic activation with right nostril breathing was also evident,although statistically not found to be significant. A statistically significant higher SDNN with left nostrilbreathing as compared to both nostril breathing (p = 0.004) was also observed. Similarly, NN50 and pNN50were found to be significantly higher with left nostril breathing as compared to both nostril breathing (p =0.003 & 0.007, respectively). However, RMSSD, LF power, HF power, LF norm, HF norm and LF/HF ratiowere not found to be statistically different for the three breathing manoeuvres.Thus our study showed an overall parasympathetic predominance, with an increase in total power of HRVwith left nostril breathing, but the minute variations of HRV were not found to be significantly differentamong the three breathing manoeuvres.